The Large Agricultural Land Plot Program and The Context of Snakeskin Gourami (Trichogaster Pectorolls) Farmers in Samut Prakan Province - Sanhapuckdee, Banjertsak; Rattanaparinyanukool, Kantigamaht; Rabob, Chutira; Vanakul , Pisanu; Yupat, Mongkhol (Business Administration and Management Journal Review, 2021)
The objectives of this article are to study the effects of the government policy toward the large agricultural land plot program to farmers and Snakeskin Gourami supply chain in Samut Prakan Province, to analyze strengths, weaknesses, problems and obstacles and to explore the opinion of farmer, processors , sellers and government’s representative to find out potential development guideline in order to get competitive advantage. This study collected 48 samples data by using survey form, questionnaires, interview and focus group. Statistically analyzed were mean, percentage, standard deviation and content analysis. Research results founded that the large agricultural land plot program created the system and mechanism cooperation between farmers and government sectors of Snakeskin Gourami supply chain. Strengths and weaknesses of policy are serious support from the government, not strong cooperation among members. The obstacles are fish species, long term period fish farming, slow growing fishes, fishes size are not up to standard, development approach for selecting their own fish species or buying from trustworthy seller, able to access funding sources, negotiation power, increase competitiveness by reducing production cost to 22.99% per kilogram, 13.22% per rai, increasing production efficiency to 11.53 %, growth and survival rate of gourami baby fishes increase 41.30%